The hybrid power mean of the quartic Gauss sums and the two-term exponential sums - Li, Xiaoxue (Advances in difference equations, 2018)
In this paper, we use the analytic method and the properties of classical Gauss sums to study the computational problems of one kind hybrid power mean of quartic Gauss sums and two-term exponential sums, and give an interesting fourth-order linear recurrence formula for it.